Pedagogical video: a key learning object for e-learning, from mediation to mediatization - Ikram, Chelliq; Omar, Erradi; Mohamed, Erradi; Mohamed, Khaldi (Frontiers in Education, 2024)
Current developments relating to integrating information and communication technologies (ICT) in learning lead us to wonder about the positive impact that pedagogical video can have on e-learning devices mediating between teacher and learner. Determining the concepts of mediatization and mediation constitutes one of the essential bases of any pedagogical engineering of mediated videos to ensure better transmission of knowledge. To articulate the two concepts of mediation and mediatization, designers, teachers, and trainers must not only mediate the contents of the video but also the pedagogical relation, the design and production process, without forgetting the scenarization phase of the pedagogical videos, which occupy an important place in the pedagogical engineering. In our article, after giving an overview of the two concepts, mediation, and mediatization, we define the pedagogical video, the use of the pedagogical video, and the forms of the pedagogical video. Then, we identify the mediatization tools of pedagogical videos and their mediatization articulation according to previous studies.